The Caenorhabditis elegans Myc-Mondo/Mad complexes integrate diverse longevity signals. - David W Johnson (Public Library of Science (PLoS), 2014)
The Myc family of transcription factors regulates a variety of biological processes, including the cell cycle, growth, proliferation, metabolism, and apoptosis. In Caenorhabditis elegans, the "Myc interaction network" consists of two opposing heterodimeric complexes with antagonistic functions in transcriptional control: the Myc-Mondo:Mlx transcriptional activation complex and the Mad:Max transcriptional repression complex. In C. elegans, Mondo, Mlx, Mad, and Max are encoded by mml-1, mxl-2, mdl-1, and mxl-1, respectively. Here we show a similar antagonistic role for the C. elegans Myc-Mondo and Mad complexes in longevity control. Loss of mml-1 or mxl-2 shortens C. elegans lifespan. In contrast, loss of mdl-1 or mxl-1 increases longevity, dependent upon MML-1:MXL-2. The MML-1:MXL-2 and MDL-1:MXL-1 complexes function in both the insulin signaling and dietary restriction pathways. Furthermore, decreased insulin-like/IGF-1 signaling (ILS) or conditions of dietary restriction increase the accumulation of MML-1, consistent with the notion that the Myc family members function as sensors of metabolic status. Additionally, we find that Myc family members are regulated by distinct mechanisms, which would allow for integrated control of gene expression from diverse signals of metabolic status. We compared putative target genes based on ChIP-sequencing data in the modENCODE project and found significant overlap in genomic DNA binding between the major effectors of ILS (DAF-16/FoxO), DR (PHA-4/FoxA), and Myc family (MDL-1/Mad/Mxd) at common target genes, which suggests that diverse signals of metabolic status converge on overlapping transcriptional programs that influence aging. Consistent with this, there is over-enrichment at these common targets for genes that function in lifespan, stress response, and carbohydrate metabolism. Additionally, we find that Myc family members are also involved in stress response and the maintenance of protein homeostasis. Collectively, these findings indicate that Myc family members integrate diverse signals of metabolic status, to coordinate overlapping metabolic and cytoprotective transcriptional programs that determine the progression of aging.